Comparative Analysis of Muslim Talaq Laws (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Muslim divorce (Talaq) has been debated and reformed worldwide.  The purpose of this article is to examine the historical, cultural, & legal foundations of Muslim talaq laws from various nations and to draw comparisons between them.  It delves into the various types of talaq, whether or not they are recognised legally, and the modern difficulties that Muslim women encounter.  The husband might face up to three years in prison for issuing an instant triple talaq (talaq-e-biddat) through any means of communication, including verbal, written, or electronic means such as email or text message.  The new law makes it easier for a victimised mother to seek financial assistance for her dependent children.  This article focuses on the development and consequences of Talaq laws in a globalised society by examining the legal frameworks in countries like Sri Lanka, Iran, Afghanistan, Pakistan, India, and Pakistan.  Even while talaq is a legitimate divorce option in the majority of these countries, several have been making strides towards more equal legal systems that give women more freedom to choose whether or not to have a divorce.